Decreased Secondary Lesion Growth and Attenuated Immune Response after Traumatic Brain Injury in Tlr2/4−/− Mice - Krieg, Sandro M.; Voigt, Florian; Knuefermann, Pascal; Kirschning, Carsten Jürgen; Plesnila, Nikolaus; Ringel, Florian (Frontiers in Neurology, 2017)
Danger associated molecular patterns (DAMPs) are released by damaged cells and trigger neuroinflammation through activation of non-specific pattern recognition receptors (PRRs), e.g. Toll-like receptors (TLRs). Since the role of TLR 2 and 4 after traumatic brain injury (TBI) is still unclear, we examined the outcome and the expression of proinflammatory mediators after experimental TBI in Tlr2/4 / and wild-type (WT) mice. Tlr2/4 / and wild-type mice were subjected to controlled cortical injury and contusion volume and brain edema formation were assessed 24 h thereafter. Expression of inflammatory markers in brain tissue was measured by quantitative PCR 15 min, 3, 6, 12, and 24 h after controlled cortical impact (CCI). Contusion volume was significantly attenuated in Tlr2/4 / mice (29.7 ± 0.7 mm³ as compared to 33.5 ± 0.8 mm³ in WT; p<0.05) after CCI while brain edema was not affected. Only interleukin-1beta gene expression was increased after CCI in the Tlr2/4 / relative to WT mice. iNOS, TNF, IL-6, and COX-2 were similar in injured WT and Tlr2/4 / mice, while the increase in HMGB1 was attenuated at 6 h. TLR 2 and 4 are consequently shown to potentially promote secondary brain injury after experimental CCI via neuroinflammation and may therefore represent a novel therapeutic target for the treatment of TBI.